Adsorption characteristics of albumin on gold and titanium metals in Hanks' solution using EQCM. Issue 4 (2004) - Lori Lori, J. A. J. A.; Hanawa Hanawa, T. T.
Abstract : The adsorption of Bovine Serum Albumin (BSA) on gold and titanium surfaces in Hanks' solution was monitored using the electrochemical quartz crystal microbalance (EQCM) technique. The changes in mass and open circuit potential at rest potential and mass and current at constant potentials were measured before and after the introduction of BSA. The mass of BSA adsorbed on titanium reached a steady value within one hour, while the albumin adsorbed on gold continued to increase. The amount of BSA adsorbed by titanium increased with concentration and stabilized at 0.8 mg/ml while that on gold did not stabilize. This indicates a monolayer of the protein on titanium and multi-layer on gold. The adsorption of BSA on gold and titanium was accelerated by the charge of potential. The time before stabilizing the adsorption‒desorption phenomena also increased with the BSA concentration.